Credit Monitoring – a Core of Credit Risk Management: Theory and Experience - Jurevičienė, Daiva; Skirckaitė, Dovilė (Vysoké učení technické v Brně, Fakulta podnikatelská, 2011)
Purpose of the article Purpose of the article is to identify credit monitoring as a keystone of credit risk management in banks. CRM is widely discussed in scientific literature and in reports of institutions undertaking credit risk or supervisory bodies. However majority of such investigations are based on implementation of numerous quantitative or qualitative methods used for credit risk assessment before granting a loan or for credit portfolio risk management. There is a lack of information or investigations made on estimation of the need of credit monitoring in credit risk management process. Scientific aim Scientific aim is to structure the early warning signs that reflect the condition of credits. Methodology/methods The paper is based on analysis and resumption of various scientific and professional articles related to organization of credit process in banks. It combines results of assessments of credit monitoring importance in credit risk management process made by theoretical studies as well as investigation of experts. Findings Finding of the article is presentation of credit monitoring tools that should be applied for corporate (and individual) clients via modification of original credit agreement. Conclusions (limits, implications etc) Conclusion of the article is that credit monitoring is a keystone in credit risk management process. The purpose of credit monitoring is to detect in time possible worsening of the loan and to react (make changes in loan agreement). The simplest tool for credit monitoring is to identify early warning signs in time that could be assorted into four groups: EWS of business environment; EWS with regard to management, EWS regarding collateral, EWS in financial analysis. Limitation of investigation is impossibility of evaluation of importance of monitoring process in practice except investigation of experts (employees) directly responsible for credit business.
Keywords: credit monitoring in banking; credit risk management; credit principles; early warning signs; monitoring tools